Neuropsychological Performance in Adolescent Marijuana Users with Co-Occurring Alcohol Use: A Three-Year Longitudinal Study - Jacobus, Joanna (Neuropsychology, 2015)
OBJECTIVE: The effect of adolescent marijuana use on brain development remains unclear despite relaxing legal restrictions, decreased perceived harm, and increasing use rates among youth. The aim of this 3-year prospective study was to evaluate the long-term neurocognitive effects of adolescent marijuana use. METHOD: Adolescent marijuana users with concomitant alcohol use (MJ+ALC, n=49) and control teens with limited substance use histories (CON, n=59) were given neuropsychological and substance use assessments at project baseline, when they were ages 16-19. They were then re-assessed 18 and 36 months later. Changes in neuropsychological measures were evaluated with repeated measures analysis of covariance (ANCOVA), controlling for lifetime alcohol use, and examined the effects of group, time, and group by time interactions on cognitive functioning. RESULTS: MJ+ALC users performed significantly worse than controls, across time points, in the domains of complex attention, memory, processing speed, and visuospatial functioning (ps<.05). Earlier age of marijuana use onset was associated with poorer processing speed and executive functioning by the 3-year follow-up (ps≤.02). CONCLUSIONS: Frequent marijuana use throughout adolescence and into young adulthood appeared linked to worsened cognitive performance. Earlier age of onset appears to be associated with poorer neurocognitive outcomes that emerge by young adulthood, providing further support for the notion that the brain may be uniquely sensitive to frequent marijuana exposure during the adolescent phase of neurodevelopment. Continued follow-up of adolescent marijuana users will determine the extent of neural recovery that may occur if use abates.